The morphology and ecology of the Carob moth (Ectomyelois ceratoniae) (Zeller) in citrus orchards of the Western Cape, South Africa - Morland, Gail (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScConsEcol)--Stellenbosch University, 2015.